Rillenkarren on Gypsum in Nova Scotia - Stenson, Ronald; Ford, Derek (Géographie physique et Quaternaire, 1993)
ABSTRACTRillenkarren are defined as densely packed, rainfall generated, bedrock channels, forming on slopes. They are usually no more than a few centimetres in width. Their lengths are dependant on the down-slope extent of exposed bedrock, Rillenkarren exist in many karst terraines on many types of rock. Rillenkarren on gypsum were measured at four differing sites in Nova Scotia. The results are compared with previous data for naturel rillenkarren on limestones. It was found that gypsum rillenkarren tend to exhibit a smaller mean width that those on limestone. Mean lenghts could not be established because rillenkarren elongation on the gypsum was limited by the length of the exposed surface. These conclusions result from the first systematic study of naturally occurring rillenkarren on gypsum and are contrary to the previously speculated dimensions reported by various authors.